2016
DOI: 10.1128/jvi.02908-15
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus and Interferon Signaling Induce Novel Autophagic Clusters in Sensory Neurons

Abstract: IMPORTANCEHerpes simplex virus type 1 (HSV-1) is a ubiquitous virus and a significant cause of morbidity and some mortality. It is the causative agent of benign cold sores, but it can also cause blindness and life-threatening encephalitis. The success of HSV-1 is largely due to its ability to establish lifelong latent infections in neurons and to occasionally reactivate. The exact mechanisms by which neurons defend against virus infection is poorly understood, but such defense is at least partially mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 92 publications
3
36
0
Order By: Relevance
“…For the study of HSV-neuron interactions, there has been significant recent focus on the sensory trigeminal ganglion or TG [36]. To achieve this, the TG must be dissected, enzymatically digested to liberate the neurons, and the neurons isolated by gradient separation.…”
Section: Introductionmentioning
confidence: 99%
“…For the study of HSV-neuron interactions, there has been significant recent focus on the sensory trigeminal ganglion or TG [36]. To achieve this, the TG must be dissected, enzymatically digested to liberate the neurons, and the neurons isolated by gradient separation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, human herpes viruses have a tendency to be latent and may be reactivated under some conditions such as weakened immunity. The reactivation of latent infections may lead to serious consequences such as postherpetic neuralgia, encephalitis, and EBV associated tumors (4)(5)(6). Moreover, many children in the world are infected with herpes viruses (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A elicits a broad array of immune responses through its metabolite, retinoic acid [Hall et al, ; Miller et al, ; Goswami and Kaplan, ], and retinol and/or retinoic acid have been shown to increase the expression of RIG‐I, and to inhibit murine norovirus replication using both in vitro and in vivo models [Lee and Ko, ]. The eye and, more precisely, the retina and optic nerve, are considered to be an extension of brain tissue [Vladan and Panfoli, ; More et al, ], and it is well‐established that HSV1 infection (the causative agent of benign cold sores) can cause blindness (HSV keratitis) and life‐threatening encephalitis [Ruderfer and Krilov, ; Katzenell and Leib, ]. Ocular viral infections are a growing problem in clinical therapy [Song et al, ].…”
Section: Introductionmentioning
confidence: 99%